The Relation of Eating Habits with Obesity in University Students - ALTIN, Mehmet (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2015)
In this study, it was aimed to determine the relation of eating habits with obesity in university students. Hereby, totally 604 students including 226 females and 378 males, studying at 5 different faculties of Selcuk University in the 2013-2014 academic year, participated in this study. The students’ heights, weights and body mass indexes (BMI) were estimated, their BMI values were calculated by dividing body weights (cm) into square meter (m²) of height. A questionnaire was applied to the relevant students in order to assess their eating habits through the BAI (Eating Habits Index) developed by Demirezen and Coşansu in 2005. The BAI internal consistency analysis the Cronbach alpha value was estimated as 0,76. To determine the differences from the total points in BAI between the female and male students, t-test was used in the independent groups; the answers to the questions by the students were expressed as percentages and frequencies. Within this study; the female students’ BMI value was found out as 26,23 ± 7,74, the male students’ BMI value was also found out as 23,43 ± 8,12, in all of the groups this value was estimated as 24,77 ± 7,02 as well. According to the reports of the World Health Organization, these values are regarded as a category of overweight ones (Table 1). While the total BAI value of females was 13,2, the BAI value of males was 12,4, when considering the all relevant students in the research, this value was calculated as 12,7. According to these results, considering the university students’ eating habits, it is concluded that males have risks at a medium level while females have higher risks of obesity.